(untitled) (The Batuk, 2021)
This article aims to prove Salman Rushdie’s Midnight’s Children as a cultural cosmopolitan novel through the lance of cosmopolitanism. Out of various types, cultural cosmopolitanism is my focus in this paper. Culturally, cosmopolitanism means openness to different cultures. Cosmopolitanism is a kind of cultural outlook involving an intellectual and aesthetic attitude of openness towards peoples, places and experiences from different cultures, especially from different nations. This type of cosmopolitanism refers to an ideal about culture or identity. Cultural cosmopolitans view that membership in a particular community is not essential for one’s social identity. It stresses that such cultural membership is irrelevant. It refers to partiality for cultures besides one’s own culture of origin as with a traveler or globally conscious person. The parochial feeling of nation and nationalism is, sometimes, an obstacle to the unity and humanitarian feeling. After the outbreak of pandemic Covid 19, people living in any corner of the world have realized- to a great extent- that the feeling of cosmopolitanism and humanism should be at the center of every human. Salman Rushdie’s Midnight’s Children evokes people, in this cosmos, cannot be confined within the boundary of limited nationalism.